Improving Speech Skills Through The Story Method for Class VII Students of SMP Negeri 3 Merauke - Nova Lina Sari Habeahan; Tobias Nggaruaka; Lay Riwu (Technium Social Sciences Journal, 2023)
The study was conducted from August until September 2020 with the aim of improving speaking skills through the storytelling method of grade VII students of SMP Negeri 3 Merauke, which amounted to 17 students. This study uses a class-action research design. Data collection is done with observations, tests, and documentation. The data is analyzed descriptively and qualitatively. The results showed that the application of storytelling methods can improve students’ speaking skills. The improvement of speaking skills can be seen in storytelling activities in learning that have fulfilled the minimum learning completion is 71. The results of the study obtained in the speaking skills of students in pre-cyclical who achieved completion only 7 people (41.8%). In the following learning, the storytelling method is demonstrated by the teacher. The yield of completion was seen to increase in cycle I, which reached 10 people (58.9%). In cycle II, there was an increase in completion to 15 people (88.24%). Thus, the application of the storytelling method can improve the speaking skills of grade VII students of SMP Negeri 3 Merauke.